Old - New Concrete Interfacial Bond Slip Monitoring in Anchored Rebar Reinforced Concrete Structure Using PZT Enabled Active Sensing - Jiang, Jian; Chen, Yixuan; Dai, Junwu (Frontiers in Materials, 2021)
Post-installed anchor technology is widely used for structural strengthening and for retroﬁtting existing constructions. The old – new concrete interface associated with using this technology is of great significance in the shear capacity of concrete structural member under shear forces. For such members, interface failures usually occur with bond slip. In this paper, an application of a piezoceramic enabled active sensing technique is put forward to monitor Old - New concrete interfacial bond slip. Three concrete specimens (S1, S2 and S3) are fabricated and each specimen consists of two parts. Each part is made of concrete poured at different times, and both are bonded with an anchored rebar embedded inside the specimen. Two PZT aggregates bonded to opposing sides of the concrete specimen helped to realize active sensing. During the shear loading test, both the load values and the signals from sensors are acquired every 20 s. The test durations of S1, S2 and S3 lasted 960s, 1120s and 1110s, respectively. Furthermore, the received signal energies are quantified through wavelet packet analysis to monitor the Old - New concrete interfacial bond slip process. The experimental results show that the change of WPEI in the received signals has a direct relation with the severity of the Old - New concrete interfacial bond slip. Moreover, the PZT-based active sensing approach is feasible to monitor the shear-induced bond slip in Old - New concrete interfaces.